Ritual dynamics in Jewish and Christian contexts : between Bible and liturgy - Bergmann, Claudia D.,; Kranemann, Benedikt, (Jewish and Christian Perspectives Series;, 2019)
Ritual Dynamics in Jewish and Christian Contexts investigates questions that arise in modern ritual studies concerning Jewish and Christian religious communities: How did their religious rituals develop? Where did different ritual communities and their ritual texts interact? How did religious communities and their authoritative texts respond to change, and how did change influence religious rituals? The volume is a product of the interdisciplinary and international research efforts taken by the Research Centre "Dynamics of Jewish Ritual Practices in Pluralistic Contexts from Antiquity to the Present" at the Universität Erfurt (Germany) and unites the voices of important senior and emerging scholars in the field. It focuses on antiquity and the medieval period but also considers examples from the early modern and modern period in Europe